The importance of physiological adaptations in the competitive success of high performance Romanian judoka athletes - Bocioaca, L. (The European Proceedings of Social & Behavioural Sciences EpSBS, 2016)
The strong link between the physiological adaptations of Romanian judo athletes who are preparing for high performance and the technical skills of the athletes is often difficult to determine and assess. Judo is a sport in which strategy and technique are dominant in obtaining performance, while the physiological characteristics and their parameters form the basis on which the judoka athlete builds the technical performance and individual tactics. The research subjects are components of judo Olympic teams from Romania, male and female. Methods of assessing anaerobic and aerobic exercise capacity are used. The research results on the effects of adaptive anaerobic effort capacity allow emphasizing the short, intensive but maximal capacity to express the muscle strength in this type of sport. The paper conclusions demonstrate the importance of adaptive effects that have occurred in the investigated athletes regarding the anaerobic and aerobic effort capacity, as an effect of intense training specific to competitive strain during a judo match, but especially during extra time periods, in those cases where the final decision has not been made in the regular time frame of five minutes. Top Romanian judoka athletes are characterized by high values of muscular strength and power, particularly in the upper parts of the body. Ideally, the judoka athletes should maintain an optimal ratio between physical preparation and technique through an optimal combination of technical and physical shape. Maintaining the optimal ratio between the training components and physical preparation ensures the most effective outcomes for obtaining high performance.